1998
DOI: 10.1016/s0741-5214(98)70126-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgical repair of ruptured abdominal aortic aneurysms in the state of Maryland: Factors influencing outcome among 527 recent cases

Abstract: The incidence of rAAA does not appear to be declining. Although operative rAAA repair continues to be associated with substantial risk and remains an especially lethal condition among the elderly, the operative mortality rate has declined in recent years in Maryland. Lower operative mortality rates and hospital charges are associated with operations performed by high-volume surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(99 citation statements)
references
References 26 publications
6
91
0
2
Order By: Relevance
“…AAA causes 15,000 deaths per year in the United States, and its incidence does not decrease over time. [4][5][6][7][8][9] An intraluminal thrombus (ILT) is present in approximately 75% of all cases of AAA. 10 Recent studies suggest that the ILT is an active pathogenic factor for AAA.…”
Section: Introductionmentioning
confidence: 99%
“…AAA causes 15,000 deaths per year in the United States, and its incidence does not decrease over time. [4][5][6][7][8][9] An intraluminal thrombus (ILT) is present in approximately 75% of all cases of AAA. 10 Recent studies suggest that the ILT is an active pathogenic factor for AAA.…”
Section: Introductionmentioning
confidence: 99%
“…[193][194][195] Circulatory failure may cause the complications of multiple organ failure, respiratory failure, renal failure, and colonic ischemia. 196,197 peutic results have been obtained owing to arch replacement using improved adjuvant measures and the recent introduction of fibrin glue and stent-grafts.…”
Section: (3) Therapeutic Resultsmentioning
confidence: 99%
“…[2][3][4] Although many attempts to evaluate the risk factors of mortality in patients with rAAA have been published, no systems or variables have proven to be reliable in the accurate prediction of mortality. Previous studies have reported that preoperative systolic blood pressure <90 mmHg, prolonged shock (e.g., >5 h), unconsciousness, and cardiac arrest are independent risk factors of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] However, the mortality of ruptured AAA (rAAA) remains high despite advances in diagnostic methods, techniques for repair including endovascular aneurysm repair (EVAR), and intensive care. 1 Previously, several factors such as age, female sex, prolonged collapsed vital phase, massive transfusion, or hemorrhage during surgery, were considered independent risk factors of mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation